Politics of the Low Countries Inaugurates the State of the Profession Section and a New Format for PhD Reviews - Vandeleene, Audrey; Meijers, Maurits J.; Russo, Luana; Ruechamps, Min (Politics of the Low Countries, 2025)
Over the past five years, the journal Politics of the Low Countries (PLC) has published original research articles (two of which are featured in this issue), research notes and literature reviews as well as PhD reviews. With this issue, PLC inaugurates a new section, entitled ‘State of the Profession’, and a new format for PhD Reviews. In this short editorial, we are delighted to present the readers these two promising sections.